KONSEP PENGEMBANGAN KAWASAN EKONOMI KHUSUS (KEK) MANDALIKA BERORIENTASI KESEJAHTERAAN MASYARAKAT LOKAL - ZULKARNAEN ZULKARNAEN; MUHAMAD SAYUTI; FAIZATUL FAJARIAH (Universitas Mahasaraswati K. Mataram, 2022)
This study aims to find the empowerment carried out by ITDC management and the Central Lombok Regency Government at every stage of the existence of the KEK Mandalika. This research is very important so that all developments carried out, including the existence of KEKs provide benefits for the welfare of the community in a sustainable manner. The existence of the KEK Mandalika as a tourism zone is absolutely oriented to the economic development of local communities, increasing local values and culture, minimizing the negative impacts of exploitation and social. The research was designed with qualitative research. Community respondents in five affected villages, including village officials. The findings obtained are that ITDC management provides broad opportunities for the community to be involved in development projects, according to the skills they have, but the facts of the willingness and skills possessed are minimal. Empowerment policies to take advantage of the operational stage by local communities, both from the government and ITDC management are still minimal. The role of the government is to use all lines of service and agencies owned to formulate community empowerment policies in realizing adequate awareness and skills, so as to benefit from the existence of the KEK Mandalika. This condition will create a mutually beneficial relationship between the community, ITDC management and the government, where community welfare can be realized, increasing community values and culture will support the existence of the KEK Mandalika. The government and ITDC management must avoid charity policies, but focus on increasing knowledge, awareness and skills in accordance with the existence of international standard KEK Mandalika tourist destinations.